Dense magnetized plasma numerical simulations - Bilbao, Luis Ernesto (2010)
The scope for developing the present numerical method was to perform parametric studies for optimization of several configurations in magnetized plasmas. Nowadays there exist several efficient numerical codes in the subject. However, the construction of one's own computational codes brings the following important advantages: (a) to get a deeper knowledge of the physical processes involved and the numerical methods used to simulate them and (b) more flexibility to adapt the code to particular situations in a more efficient way than would be possible for a closed general code. The code includes ion viscosity, thermal conduction (electrons and ions), magnetic diffusion, thermonuclear or chemical reaction, Bremsstrahlung radiation, and equation of state (from the ideal gas to the degenerate electron gas). After each calculation cycle, mesh vertices are moved arbitrarily over the fluid. The adaptive method consists of shifting mesh vertices over the fluid in order to keep a reasonable mesh structure and increase the spatial resolution where the physical solution demands. The code was a valuable tool for parametric study of different physical problems, mainly optimization of plasma focus machine, detonation and propagation of thermonuclear reactions and Kelvin-Helmholtz instabilities in the boundary layer of the terrestrial magnetopause. © 2010 IOP Publishing Ltd.